Evaluation of exoenzyme profiles of Candida albicans species isolated from females with vaginal candidiasis - Hasti Nouraei; Leila Razeghian Jahromi; Mehdi Ghaderian Jahromi; Kamiar Zomorodian; Keyvan Pakshir (Mazandaran University of Medical Sciences, 2024)
Background and Purpose: The three most common causes of vaginitis are bacteria, yeast, and Protozoa. Candida albicans is one of the most common causes of vaginitis and commonly affects millions of females with different signs and symptoms. Secretion of exoenzymes from Candida species plays an important role in virulence and pathogenesis. Increasing our knowledge about the pathogenesis of candidiasis could help to design new anti-Candida drugs. This study aimed to evaluate the phospholipase, esterase, and hemolysin activities of the vaginal Candida isolates and their correlation with the presence of vulvovaginal candidiasis.Materials and Methods: In total, 119 Candida albicans isolates from vaginal candidiasis were enrolled in the study. Egg yolk agar, Tween 80 opacity medium, and blood agar plate assays were used for the determination of phospholipase, esterase, and hemolytic activities, respectively.Results: Based on the findings, 110 (92.44%) isolates showed phospholipase activity, 93 (78.2%) isolates were esterase producers, and 90 (75.6%) species had hemolytic activity.Conclusion: This study showed that most of the tested isolates had different enzymatic patterns. Discrimination of variations in the production of these exoenzymes among different Candida isolates may depend on Candida spp. pathogenicity and could be responsible for the severity of symptoms among the patients.